1999
DOI: 10.1103/physreva.60.r3381
|View full text |Cite
|
Sign up to set email alerts
|

Optical generation of vortices in trapped Bose-Einstein condensates

Abstract: W e dem onstrate num eri cal l y the e ci ent generati on of vorti ces i n B ose-Ei nstei n condensates (B EC ) by usi ng a \phase i m pri nti ng" m ethod. T he m ethod consi st of passi ng a far o resonant l aser pul se through an absorpti on pl ate w i th azi m uthal l y dependent absorpti on coe ci ent,i m agi ng the l aserbeam onto a B EC ,and thuscreati ng the correspondi ng non-di ssi pati ve Stark shi ftpotenti al and condensate phase shi ft. In ourcal cul ati onsw e take i nto accountexperi m entali m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
214
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 205 publications
(217 citation statements)
references
References 30 publications
3
214
0
Order By: Relevance
“…In order to nucleate vortices, the trapped gas can be rotated at temperatures above the BEC transition. Recently, it has been suggested that vorticity could be imprinted by imaging a BEC through an absorption plate [186]. The method consists of passing a far-off-resonant laser pulse through an absorption plate with an azimuthally dependent absorption coefficient, imaging the laser beam onto a BEC, and thus creating the corresponding nondissipative Stark-shift potential and condensate phase shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to nucleate vortices, the trapped gas can be rotated at temperatures above the BEC transition. Recently, it has been suggested that vorticity could be imprinted by imaging a BEC through an absorption plate [186]. The method consists of passing a far-off-resonant laser pulse through an absorption plate with an azimuthally dependent absorption coefficient, imaging the laser beam onto a BEC, and thus creating the corresponding nondissipative Stark-shift potential and condensate phase shift.…”
Section: Discussionmentioning
confidence: 99%
“…Also the vortex state can be detected by the splitting of the collective condensate modes in axisymmetric traps [62,111,115] or by looking at the phase slip in the interference fringes produced by two expanding condensates [167,70]. Dobrek et al [186] proposed an interference method to detect vortices by coherently pushing part of the condensate with optically induced Bragg scattering. A detection scheme that reveals the existence of vortex states in a cylindrically symmetric trap is discussed by Goldstein, Wright and Meystre [193].…”
Section: Discussionmentioning
confidence: 99%
“…In this way one can imprint the desired phase structure on the condensate and hence create a dark soliton [22,23].…”
Section: A Phase Imprintingmentioning
confidence: 99%
“…Let us review here how the phase imprinting can lead to the creation of a soliton [22]. For a laser pulse duration shorter than the correlation time of the condensate τ cor =h/µ, where µ is the chemical potential, the wave function acquires a local phase factor e −iφ without changing the condensate's density profile.…”
Section: A Phase Imprintingmentioning
confidence: 99%
See 1 more Smart Citation